A Review of Mental Health Issues in High-Performance and Elite-Level Cycling - Smith, Alexander; Buadze, Ana; Colangelo, Jill; Liebrenz, Michael (International Journal of Sports Medicine, 2023)
Despite the public health benefits of cycling in the general population, mental health issues may be evident in high-performance and elite-level competitive domains. With prominent riders disclosing their experiences with psychiatric symptoms, distinctive socioenvironmental factors could exacerbate psychopathological vulnerabilities. This suggests a need for greater mental health awareness amongst stakeholders, supplemented by actions from international and national federations and regulators. To synthesise relevant observations about psychiatric concerns in high-performance and elite-level cycling, we conducted a keyword search of articles in APA PsycINFO, PubMed, and Scopus based on specified exclusion criteria. Thirteen papers were identified that examined mental health issues in high-performance and/or elite-level cycling per classifications from the World Health Organization’s International Classification of Diseases 11th Revision. A large proportion of articles illustrated eating disorder symptomatology, but others discussed attention deficit/hyperactivity disorder, anxiety disorder, depression, sleep wake disorders, and substance use disorder. Existing literature underlines important considerations for all stakeholders within the cycling community around mental health initiatives and care provisions, which are currently lacking across the sport. Such programmes could incorporate consensus statements, psychiatric screening, psychoeducation, stigma-reducing policies, and athlete advocacy. These can help mitigate socioenvironmental risk factors and prioritise athlete wellbeing over performance-centred motivations.
Keywords: mental health; sports psychiatry; eating disorders; risk factors; psychoeducation